Design of Toll Road Embankment With Secondary Compression Mitigation After Pvd Installation and Solutions For The Probolinggo – Banyuwangi Toll Road Construction Project Package 2 Sta 16+300 – Sta 16+700 - Aryandi, Septya Kukuh; Mochtar, Indrasurya B.; Endah, Noor; Artanto, Abdjad Agung (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
In the Probolinggo-Banyuwangi Toll Road construction project package 2, there are several areas where the subgrade consists of soft soil, one of which is at STA 16+300 – STA 16+700. In this section, soft soil with a depth of up to 12 meters is found. The primary issue in constructing on soft soil is settlement. Settlement occurs due to the high compressibility of clay, where consolidation takes an extended period. This condition may pose problems during both the construction and operational phases of the toll road due to ongoing settlement.Consolidation consists of primary consolidation and secondary compression. Primary consolidation occurs first, followed by secondary compression. The method used in this study to accelerate primary consolidation and secondary compression involves prefabricated vertical drains (PVD) combined with preloading. The study was conducted at STA 16+300 – STA 16+700, where compressible soil with a depth of 12 meters is present, but the embankment height varies. For this study, embankment heights of 4m, 6m, and 8m were analyzed. Once the magnitude of primary consolidation and secondary compression from year 2 to year 15 was determined, the results were evaluated based on the Binamarga standards. Specifically, the settlement requirements are as follows: during the 2nd and 3rd years, settlement must be less than 2 cm; during the 2nd and 12th years, it must be less than 10 cm with a construction period of 2 years and maintenance of 1 year; and during the 5th and 6th years, it must be less than 2 cm; while during the 5th and 15th years, it must be less than 10 cm with a construction period of 3 years and maintenance of 2 years. From these results, the required embankment heights for which preloading is necessary were identified.Slope stability analysis for the embankment was also conducted to determine whether the stability meets the required standards. If the stability requirements were not met, reinforcement using geotextile material was applied. Therefore, for each embankment variation, the necessary amount of geotextile was determined.The results of this study show that the settlement requirements of Binamarga were met during the 2nd and 3rd years, the 5th and 6th years, and the 5th and 15th years, but not during the 2nd and 12th years, indicating the need for preloading. Regarding embankment stability, the factor of safety for all embankment variations was found to be below the required standard, necessitating the use of geotextile reinforcement. Based on these results, this study serves as input for selecting the appropriate method and ensuring a faster implementation period for the toll road construction.